Skin-friendly and highly fireproof fabric up to 1142 °C weaved by basalt @ polyimide yarns. (November 2022) - Wang, Kai; Fu, Chiyu; Xu, Ao; Wu, Minyong; Jia, Lili; Xu, Weilin; Su, Bin; Xia, Zhigang
Abstract: Progress in fighting against fires depends on the development of novel fabrics with the balance between the wearing comfort and the fireproof capabilities, which is a particular challenge for protecting the safety of firefighters. However, current organic fabrics are easy to burn at high temperatures while inorganic fireproof fabrics are too brittle to wear comfortably. Therefore, the development of skin-friendly, highly fireproof fabrics is urgently required. In this paper, we report an inorganic/organic composite fabric weaved by basalt@polyimide yarns (denoted BS@PI yarns) that is skin-friendly and highly fireproof up to 1142 °C, which is much higher than that of commercial Aramid 1313. The BS@PI yarns are prepared through a non-destructive spinning method, allowing the brittle yet fireproof BS core surrounded by a soft PI sheath. Owing to the existence of the PI sheath, the as-prepared fabric shows good skin compatibility, high fire resistance, and well mechanical properties. Even being rubbed for 300 cycles, the BS@PI fabric is still skin-friendly without broken & sharp BS burrs towards the users. By using the inorganic-core@organic-sheath yarn strategy, our BS@PI fabric exhibit persistent skin-friendly and highly fireproof capability, which has great potential for use in protective clothing for emergency-service personnel. Graphical abstract: BS@PI yarn weaved fabric exhibit persistent skin-friendly and highly fireproof capability. Image 1